Applications of cellulose nanomaterials in pharmaceutical science and pharmacology - Y. Cao (eXPRESS Polymer Letters, 2018)
Cellulose nanomaterials (CNs) have been successfully applied to a variety of scientific areas in recent years with remarkable engineering utilities. As sustainable materials of huge abundance, CNs show significant potentials in fine-tune the microstructures and kinetics from the nano-level. This paper reviews recent key advancements of the use of CNs in the fields of pharmaceutical science and pharmacology. A broad overview of the development of CNs is provided, and the current methods to obtain the materials are discussed. The different types of processing techniques are reviewed, that are critical to the applications in pharmaceutical science and pharmacology. The key breakthroughs of applications in major fields are discussed, including oral administration, topical administration, tissue scaffolds, and antibacterial applications.